Jelajah Prihatin UMP helps Kerdau community - Nor Salwana, Mohammad Idris (2022)
TEMERLOH, 27 June 2022 - Jelajah Prihatin UMP with the Kerdau Community provided an opportunity for university students and staff to be with the community to conduct programmes after almost two years of being put on hold due to the spread of COVID-19.